2023
DOI: 10.1038/s41467-023-36436-w
|View full text |Cite
|
Sign up to set email alerts
|

Emergent collective organization of bone cells in complex curvature fields

Abstract: Individual cells and multicellular systems respond to cell-scale curvatures in their environments, guiding migration, orientation, and tissue formation. However, it remains largely unclear how cells collectively explore and pattern complex landscapes with curvature gradients across the Euclidean and non-Euclidean spectra. Here, we show that mathematically designed substrates with controlled curvature variations induce multicellular spatiotemporal organization of preosteoblasts. We quantify curvature-induced pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 65 publications
(98 reference statements)
1
16
0
Order By: Relevance
“…[39] In a very recent work, Callens et al demonstrated that mathematically designed substrates exhibiting controlled curvatures were able to induce multicellular spatiotemporal organization of MC3T3-E1. [40] In our case, the edges of P80 replicas mimicked gyroid surface features found in osteons and trabecular bone. Clearly, on the convex edges, cells have lost their cuboidal shape, a morphological characteristic of mature osteoblasts.…”
Section: Pdms Curvature Guided Mc3t3-e1 Morphologysupporting
confidence: 69%
See 1 more Smart Citation
“…[39] In a very recent work, Callens et al demonstrated that mathematically designed substrates exhibiting controlled curvatures were able to induce multicellular spatiotemporal organization of MC3T3-E1. [40] In our case, the edges of P80 replicas mimicked gyroid surface features found in osteons and trabecular bone. Clearly, on the convex edges, cells have lost their cuboidal shape, a morphological characteristic of mature osteoblasts.…”
Section: Pdms Curvature Guided Mc3t3-e1 Morphologysupporting
confidence: 69%
“…The influence of surface curvature upon osteogenic gene expression have been reported in numerous work [ 6,7,40 ] Overall, it was demonstrated that a convex curvature leads to a cell bending that imposes morphological changes to nucleus such that it flattens and adopts a shrunken bean‐like shape. Subsequently, the external forces exerted upon the nucleoskeleton through cell morphology changes activate mechanotransduction signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, drug treatments affecting the cellular contractility may have altered the rupture strength of cell-substrate adhesion because of the mutual interaction between cellular force and mechanosensitive molecular complex, e.g., focal adhesions [63], formed at the cellsubstrate interface. Also, substrate curvature at this supracellular scale is recently known to influence cell differentiation [64,65], which potentially changes the magnitude of cell contraction. Such interdependency of the experimental parameters may have resulted in some minor features of the probability maps that our model did not predict; there is a constant probability of adhesion over the different curvatures in the presence of TGF-β (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the availability of a wide range of materials (i.e., biocompatible polymers) and the ability of these techniques to print at very high resolutions with minimum feature sizes in the micron range. , Examples of these techniques are stereolithography (SLA) , and two-photon polymerization (2PP). ,, Different meta-biomaterials with 3D multiscale features and sizes down to submicron ranges have been 3D printed using 2PP. The 2PP AM technique, like other similar light-assisted techniques, can be combined with conventional manufacturing techniques (e.g., molding) in a hybrid fashion to push the boundaries of the existing 3D printing techniques. This approach has been used, for example, to study the curvature-dependent mechanobiology of bone cells at the microscale, by integrating molded 2PP 3D printed structures and creating soft elastomeric microsurfaces . This approach can be further extended to develop meta-biomaterials with tunable morphological and material properties in the future.…”
Section: Micro-am Technology To Fabricate Meta-biomaterialsmentioning
confidence: 99%